Eksistensi Penyajian Polopalo sebagai Alat Musik Tradisional Gorontalo - Karlan, La Ode (Jurnal Bahasa, Sastra, dan Budaya, 2025)
Polopalo is one of Gorontalo’s traditional musical instruments that carries significant historical, aesthetic, and cultural values. This instrument functions not only as a form of entertainment but also as a medium of cultural communication, local identity, and tradition preservation. This study aims to explore the existence of polopalo performances within Gorontalo society, focusing on its functions, performance forms, and roles amidst social changes. The research employed a qualitative method with an ethnographic approach through observation, interviews, and documentation. The findings reveal that polopalo continues to exist as part of Gorontalo culture, although it faces challenges from modernization and the lack of young musicians’ regeneration. Its performances are now mostly found in traditional ceremonies, cultural festivals, and as an educational medium in schools. Therefore, polopalo is not only a traditional musical instrument but also a symbol of Gorontalo’s identity and local wisdom that must be preserved.